Elucidation on antioxidant and antidiabetic activities of Curculigo latifolia dryand via in vitro and molecular docking - Zabidi, Nur Athirah (2020)
Type 2 diabetes mellitus (T2DM) is a heterogeneous metabolic disorder, causing various health complications, and apparently affects the human’s life. The controversy over taking antidiabetic medications for diabetic patients has a definite side effect on either short-term or long-term effects. Despite a wide solution that has revealed in providing systematic relief in T2DM, considerable research attention has been focussing on exploring a better therapeutic alternative research that generally employed to increase antidiabetic values from the natural plant extract. The aim of the current study was to elucidate on antioxidant and antidiabetic activities on root and fruit extracts of Curculigo latifolia via in vitro and molecular docking studies. The evaluation in the phytochemical and antioxidant activity has been assessed by total flavonoid content (TFC), total phenolic content (TPC), 2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. Besides, antidiabetic activity was subsequently explored based on the inhibition of α-amylase, α-glucosidase and dipeptidyl peptidase (IV) assay, along with in vitro studies through glucose uptake activity, insulin secretion assay and screening agonist of Peroxisome proliferator-activated receptor gamma (PPAR-γ). Then, the activity of the protein was further assessed through molecular docking analysis with the selected ligands from the screening of compounds using liquid chromatography-mass spectrometry (LCMS). The effect of subcritical water extraction (SWE) temperature on TPC, TFC and antioxidant capacity (ABTS & DPPH) shows a significant (p < 0.05) while the extraction’s times shows no significant effect.The highest results for the root extracts recorded with extraction yield (36.5g/100g), TPC (92.55 mg GAE/g), TFC (13.26 mg RE/g) ABTS (66.8 mg trolox equiv/g) and DPPH (128.7 mg trolox equiv/g) at 180oC and 30 minutes extraction time. Conversely, the highest results for the fruit extracts recorded with extraction yield (16.7g/100g), TPC (78.63 mg GAE/g), TFC (5.79 mg RE/g) ABTS (54.8 mg trolox equiv/g) and DPPH (127.3 mg trolox equiv/g) also at 180oC and 90 minutes extraction time. Moreover, a significant positive correlation between TPC, TFC and antioxidant capacity (DPPH and ABTS) values was detected for both of the extracts. In an enzymatic assay, both extracts show a significant positive inhibition (p < 0.05). The highest inhibition by the roots extracts with α-glucosidase (IC50 2.72±1.43 mg/ml), α-amylase (IC50 0.31±2.31 mg/ml), DPP (IV) (IC50 3.9±0.95 mg/ml) compared with fruit extract that recorded with α-glucosidase (IC50 5.6±0.66 mg/ml), α-amylase (IC50 1.3±0.75 mg/ml), DPP (IV) (IC50 5.7±0.66 mg/ml). In addition, both of the extracts caused a significant increase (p< 0.05) in glucose uptake activity in adipocyte 3T3-L1 and L6 cell lines. The highest glucose uptake by 3T3-L1 for the root and fruits extract was 67% and 49% respectively. Meanwhile, the highest glucose uptake by L6 muscle cells for the root extract was 85% while for the fruit extract was 68%. Besides, both of the extracts displayed a significant increase (p< 0.05) in insulin secretion with the highest activity by the root and fruit was 13.74 μg/ml and 11.06 μg/ml respectively in pancreatic BRIN-BD11cell line. The results on the screening of ppar-γ agonist assay show that root extracts exhibit 25%, and fruit extracts give 14% significance with p ≤ 0.05 by comparing both of the extracts. Molecular docking results indicated that phlorizin, scandenin, pomiferin and mundulone were selected as a potential inhibitor in most of the targeted protein by having the least binding energy and some of these ligands were observed that interact with crucial residues in the active site region of the protein. In conclusion, the present study indicated that there is potential in the development of C. latifolia as a therapeutic alternative agent for T2DM management, particularly by benefiting the simultaneous targeting in the main mechanism of action in T2DM.